Environmental Management in Construction A quantitative approach - Li, Heng (Taylor & Francis, 2006)
Demands on the construction industry are changing, and it is now virtually essential for environmental management to be considered at all stages of a project. Many construction managers are finding a quantitative approach useful, and this book outlines four quantitative methods which can be applied at different construction stages, and which fit within a comprehensive framework of dynamic Environmental Impact Assessment (EIA). These include: a method to quantitatively evaluate and reduce pollution and hazards levels a method to evaluate the environmental-consciousness of proposed construction plans a method to reduce on-site construction wastes through an incentive reward programme a method to promote C and D waste exchange in the local construction industry. With an experimental case study of the application of these methods, this book delivers a comprehensive review of environmental management issues in construction. With regulatory requirements potentially favouring the quantitative approach, this timely guide ensures that contractors will be able to keep pace with environmental management standards.